Novel stereoisomeric lignin-derived polycarbonates: towards the creation of bisphenol polycarbonate mimics. Issue 8 (17th January 2023) - Wu, Xianyuan; Xu, Dan; De bruyn, Mario; Trimmel, Gregor; Barta, Katalin
Abstract : We have described a family of bio-based and property-tunable polycarbonates (PC-MBC) based on the novel stereoisomeric lignin-derived aliphatic diol 4, 4′-methylenebiscyclohexanol (MBC) that was sustainably sourced from lignin oxidation mixture. Abstract : In this work, we have described a family of bio-based polycarbonates (PC-MBC) based on the unique lignin-derived aliphatic diol 4, 4′-methylenebiscyclohexanol (MBC) that was sustainably sourced from lignin oxidation mixture. The detailed structure analysis of these polycarbonates has been confirmed by a series of 2D NMR (HSQC and COSY) characterizations. Depending on the stereoisomerism of MBC, the PC-MBC displayed a wide achievable T g range of 117–174 °C and high T d5% of >310 °C by variation of the ratio of the stereoisomers of MBC, offering great substitution perspectives towards a bisphenol-containing polycarbonates. Nonetheless, the most here presented PC-MBC polycarbonates were film-forming and transparent.